Selection and Characterization of Palmitic Acid Responsive Patients with an OXPHOS Complex I Defect - Theunissen, Tom E. J.; Gerards, Mike; Hellebrekers, Debby M. E. I.; van Tienen, Florence H.; Kamps, Rick; Sallevelt, Suzanne C. E. H.; Hartog, Elvira N. M. M.-D.; Scholte, Hans R.; Verdijk, Robert M.; Schoonderwoerd, Kees; de Coo, Irenaeus F. M.; Szklarczyk, Radek; et al. (Frontiers in Molecular Neuroscience, 2017)
Mitochondrial disorders are genetically and clinically heterogeneous, mainly affecting high energy-demanding organs due to impaired oxidative phosphorylation (OXPHOS). Currently, effective treatments for OXPHOS defects, with complex I deficiency being the most prevalent, are not available. Yet, clinical practice has shown that some complex I deficient patients benefit from a high-fat or ketogenic diet, but it is unclear how these therapeutic diets influence mitochondrial function and more importantly, which complex I patients could benefit from such treatment. Dietary studies in a complex I deficient patient with exercise intolerance showed increased muscle endurance on a high-fat diet compared to a high-carbohydrate diet. We performed whole-exome sequencing to characterize the genetic defect. A pathogenic homozygous p.G212V missense mutation was identified in the TMEM126B gene, encoding an early assembly factor of complex I. A complementation study in fibroblasts confirmed that the p.G212V mutation caused the complex I deficiency. The mechanism turned out to be an incomplete assembly of the peripheral arm of complex I, leading to a decrease in the amount of mature complex I. The patient clinically improved on a high-fat diet, which was supported by the 25% increase in maximal OXPHOS capacity in TMEM126B defective fibroblast by the saturated fatty acid palmitic acid, whereas oleic acid did not have any effect in those fibroblasts. Fibroblasts of other patients with a characterized complex I gene defect were tested in the same way. Patient fibroblasts with complex I defects in NDUFS7 and NDUFAF5 responded to palmitic acid, whereas ACAD9, NDUFA12 and NDUFV2 defects were non-responding. Although the data are too limited to draw a definite conclusion on the mechanism, there is a tendency that protein defects involved in early assembly complexes, improve with palmitic acid, whereas proteins defects involved in late assembly, do not. Our data show at a clinical and biochemical level that a high fat diet can be beneficial for complex I patients and that our cell line assay will be an easy tool for the selection of patients, who might potentially benefit from this therapeutic diet.